(untitled) (Journal of Informatics Education and Research, 2025)
This research intended to study the impact of healthcare information technology on digital health maintenance organization in the state of Kuwait. Furthermore, with the calculated insights from this study we intended to solve identified problems not limited to increased patient and provider spending and unify the quality of care and optimally utilization of resources. The approach in this research was a combination of quantitative surveys and qualitative interviews for data collection. The healthcare professionals, Healthcare IT professionals and Healthcare business associates were provided by surveys to evaluate their current utilization, understanding, usability and satisfaction of healthcare technology solutions in place along with detailed challenges and realized benefits. The sole intention was to obtain detailed insights of Health maintenance organizations understanding, design and practicality.